CFD studies on natural convection heat transfer of Al2O3-water nanofluids - Walvekar , Rashmi Gangasa; Ismail, Ahmad Faris; Mohamed, Khalid; Yusof, Faridah (Springer, 2011)
This work is focused on numerical simulations of natural convection heat transfer in Al2O3-water nanofluids using computational fluid dynamics approach. Fluent v6.3 is used to simulate water based nanofluid considering it as a single phase. Thermo-physical properties of the nanofluids are considered in terms of volume fraction and size of nanoparticles, size of base fluid molecule and temperature. The numerical values of effective thermal onductivity have also been compared with the experimental values available in the literature. The numerical result simulated shows decrease in heat transfer with increase in particle volume fraction. Computed result shows similar trend in increase of Nusselt number with Relayigh number as depicted by experimental results. Streamlines and temperature profiles are plotted to demonstrate the effect.